Answer:
- 58 kJ
Step-by-step explanation:
The equation of the reaction is given as;
2NO2(g) → N2O4(g)
N2(g) + 202(g) → 2NO2(g) delta H = 67.7 kJ
Since NO2 is the reactant in the equation, we have to reverse this reaction. We now have;
2NO2(g) → N2(g) + 202(g) delta H = - 67.7 kJ
N2(g) + 202(g) → N2O4(g) delta H = 9.7 kJ
Since NO4 is the product in the equation, we don't have to do anything to this reaction.
Adding the two reactions;
2NO2(g) → N2(g) + 202(g) delta H = - 67.7 kJ
N2(g) + 202(g) → N2O4(g) delta H = 9.7 kJ
---------------------------------------------------------------- N2(g) and 2O2 (g) cancels out
2NO2(g) → N2O4(g) delta H = (-67.7 + 9.7) = - 58 kJ